Napovedna vrednost števila celic CD34+ v krvi bolnika/darovalca pred zbiranjemkrvotvornih matičnih celic z levkaferezami - Domanovič, Dragoslav (Zdravniški vestnik, 2004)
Background. In the study we tried to define a predictive value of the circulating CD34+ cells in patients/donors blood for estimation of the hematopoietic stem cells (HSC) collection efficacy determine the optimal time to initiate the collection by leukapheresis procedure. Methods. We retrospectively analyzed 75 collections of HSC using the Amicus cell separatorin 39 patients and 15 donors. Circulating CD34+cell counts in patients/donors were compared to the achieved CD34+ cell yields to determine its predictive value for the collection of a targeted yield of > 2 x 10 6 CD34+ cells/kg body weight of patient. Results. The results of cell counts confirmed that mobilization regimens were successful and HSC collections efficient High correlation coefficient (r = 0.82) between the number of circulating CD34+ cells before collection and CD34+ cell yield/kg of patient'sbody weight was statistically significant (p < 0.05). With ROC analysis we determined the cut-off value 42 x 10 6/L CD34+ cell counts in the blood of patients/donors before collection that had a positive predictive value 87% and a negative predictive value 91.6%. Conclusions. Analysis showed that the number of circulating CD34+ cells before the procedure express a veryhigh predictive value and can be used for determining the optimal time to initiate collection of HSC by leukapheresis.
Keywords: Antigeni, CD34; Antigens, Cd34; Blood Donors; Hematopoetske matične celice; Hematopoietic Stem Cells; Krvodajalci; Leukapheresis; Levkofereza; Retrospective Studies; Retrospektivne študije